Lycium barbarum Ameliorates Neural Damage Induced by Experimental Ischemic Stroke and Radiation Exposure - Yan Huang; Xing Zhang; Ling Chen; Bo Xu Ren; Feng Ru Tang (Frontiers in Bioscience-Landmark, 2023)
Ischemic stroke and cranial radiotherapy may induce brain inflammatory response, oxidative stress, apoptosis and neuronal loss, and impairment of neurogenesis. Lycium barbarum has anti-oxidation, anti-inflammatory, anti-tumor and anti-aging properties, may produce both neuroprotective and radioprotective effects. In this narrative review paper, we described the neuroprotective effect of Lycium barbarum in different animal models of experimental ischemic stroke and limited studies in irradiated animal models. Relevant molecular mechanisms are also summarized. It has been shown that in experimental ischemic stroke models, Lycium barbarum produces neuroprotective effects by modulating neuroinflammatory factors such as cytokines and chemokines, reactive oxygen species, and neurotransmitter and receptor systems. In irradiation animal models, Lycium barbarum prevents radiation-induced loss of hippocampal interneurons. Given its minimal side-effects, these preclinical studies suggest that Lycium barbarum may be a promising radio-neuro-protective drug that can be used as an adjunct treatment to radiotherapy for brain tumor and in the treatment of ischemic stroke. At molecular levels, Lycium barbarum may regulate PI3K/Akt/GSK-3β, PI3K/Akt/mTOR, PKCε/Nrf2/HO-1, keap1-Nrf2/HO-1, and NR2A and NR2B receptor- related signal transduction pathways to produce neuroprotective effects.